An examination of the Social Skills Improvement System-Rating Scale (SSIS-RS) teacher and parent forms factor structure in a sample of Mexican American preschool-aged children - Hanjoe Kim; Jacqueline R. Anderson; Jorge E. Gonzalez (PLoS ONE, 2025)
Social skills assessment has become integral to childhood mental health evaluation and a target for interventions, especially among school psychologists. One popular multi-rater social skill instrument is the Social Skills Improvement System Rating Scales (SSIS-RS), which is designed to evaluate social skills, problem behaviors, and academic competence in children. While previous versions of the SSIS have been widely used in research and practice, including use with translations across multiple languages, few studies have examined the psychometric properties of the most recent iteration of the SSIS-RS with diverse populations. The current study used the Spanish Parent and English Teacher versions to assess its construct validity with a Mexican American population. Confirmatory factor analysis conducted with data from 624 parents and 135 teachers rating 761 Mexican American children’s social skills and problem behaviors revealed adequate psychometric properties but varied somewhat from the proposed scale models of the SSIS-RS. The differences may be due to the cultural uniqueness of Mexican origin compared to the norming sample. Further, similarities and discrepancies were found when comparing the factor structures between parent and teacher ratings. These results suggest that while parents and teachers shared views on the children, environmental factors and the language of the SSIS-RS might have influenced their responses.